The Role of Person-Vocation Fit in the Relationship Between Human Resources Management Practices and Career Commitment: A Study in Hotel Businesses - Akça, İbrahim; Demir, Yeliz; Demir, Özkan (Fırat University, 2025)
The universe of this study, which was conducted to determine the role of person-vocation fit in the relationship between human resources management practices and career commitment, consists of five-star hotels operating in Istanbul. A survey data collection tool was used to collect data in the study, 397 hotel employees were reached and the obtained data were analyzed through a statistical program. Before conducting the analyses in the study, the internal consistency coefficient (Alpha) for the scales used was calculated and the expressions that disrupted the reliability of the scale were removed from the analyses. The research model in which the relationships between the variables were constructed was tested with the help of the PROCESS MACRO package program. Before testing the moderator effect model, it was examined whether the data had a normal distribution and it was determined that the data had a normal distribution. The sample largely consisted of young, single and male participants, and approximately 70% of them declared that their experience in their current institutions was more than 3 years. As a result of the research analyses, it was determined that human resources management practices increased career commitment. The research also determined that the moderating role of person-vocation fit in the relationship between human resources management practices and career commitment is not statistically significant.

İnsan kaynakları yönetimi uygulamaları ile kariyer bağlılığı ilişkisinde kişi-meslek uyumunun rolünün belirlenmesi amacıyla gerçekleştirilen bu araştırmanın evreni İstanbul’da faaliyet gösteren beş yıldızlı otellerden oluşmaktadır. Araştırmada verilerin toplanmasında anket veri toplama aracı kullanılmış, 397 otel çalışanına ulaşılmış ve elde edilen veriler istatistiki program aracılığıyla analiz edilmiştir. Araştırmada analizler yapılmadan önce kullanılan ölçeklere ilişkin iç tutarlılık kat sayısı (Alpha) hesaplanmış ölçek güvenirliğini bozan ifadeler analizlerden çıkartılmıştır. Değişkenler arası ilişkilerin kurgulandığı araştırma modeli PROCESS MACRO paket programı yardımıyla test edilmiştir. Düzenleyici etki modelinin test edilmesinden önce verilerin normal dağılıma sahip olup olmadığı incelenmiş ve verilerin normal dağılıma sahip olduğu belirlenmiştir. Örneklem büyük oranda genç, bekâr ve erkek katılımcılardan oluşmakta olup, yaklaşık %70’i mevcut kurumlarında deneyim süresinin 3 yıldan fazla olduğunu beyan etmiştir. Araştırma analizleri sonucunda insan kaynakları yönetimi uygulamalarının kariyer bağlılığını arttırdığı belirlenmiştir. Araştırmada ayrıca insan kaynakları yönetimi uygulamaları ile kariyer bağlılığı ilişkisinde kişi meslek uyumunun düzenleyici rolünün istatistiki olarak anlamlı olmadığı belirlenmiştir.
İnsan Kaynakları Yönetimi Uygulamaları ile Kariyer Bağlılığı İlişkisinde Kişi-Meslek Uyumunun Rolü: Otel İşletmelerinde Bir Araştırma
Keywords: Marketing (Other); Pazarlama (Diğer)